THEORETICAL AND METHODOLOGICAL APPROACHES TO THE FORMATION OF STUDENTS OF SCIENTIFIC CONCEPTS IN PHYSICS LESSONS - Lyasov, I.H. (Pedagogy of Higher and Secondary Education, 2022)
In article problems, ways and means of formation at pupils of scientific concepts are analyzed. The author considers both the common and pedagogical approaches, and questions of a methodical of physics in the school.